MOBILE APPLICATIONS FOR TASKS OF DISTANCE LEARNING - T. A. Demenkova; V. S. Tomashevskaya; I. S. Shirinkin (Российский технологический журнал, 2018)
The article considers the actual problem of transferring some tasks of the distance learning onto a mobile platform. The research was carried out on the basis of several generations of custom-designed software for the preparation of masters on the direction «Informatics and Computer Technlolgy» within the framework of the program «Architecture of Computer Technology and Information Systems». The paper describes the technology for developing and implementing a mobile application for a distance learning system for smartphones running the Android operating system. The task was to apply the system for the organization of distance learning in the international double-degree program in the framework of cooperation with foreign universities. The specificity of such an application lies in the possibility of teaching in English using software to combine the two training programs of participating universities to form individual training plans depending on the previous master's knowledge. It is planned to include special developments, for example, the use of task solvers to reduce the burden on teachers accompanying the learning process. This will reduce the time when solving difficult tasks as related to hardware implementation of algorithms for digital processing of information. Thus, we can speak about the expansion of the research part of this scientific project and the emerging possibility of using a mobile application for research and implementation of practices for obtaining professional skills and professional experience that occupy a significant place in the curriculum of undergraduates. The approach and methodology are proposed for implementing an individual distance learning system based on standard application modules using emulators. The results of experiments according to key parameters of the program system are presented.